Analisis Hubungan Pariwisata dan Pertumbuhan Ekonomi terhadap Emisi CO2 di Indonesia - Mela Dipa Sekar Putri; Rida Oktayanti; Suci Amalia; Hilda Amalia (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2019)
The purpose of this study is to empirically examine how the relationship of tourism's influence and economic growth on CO2 emissions. In this case the data used by researchers is the researchers took some data on the number of foreign tourists coming to Indonesia and the economic growth that exists in Indonesia to CO2 emissions in Indonesia. This study also examines the Environmental Kuznets Curve (EKC) hypothesis between tourism income and CO2 emissions. To achieve this goal, researchers used econometric regression techniques. The method used is using the OLS (Ordinary Least Square) method and data using annual data (time series). In the results obtained get 2 results namely the level of economic growth (x1) has a positive and significant effect on the level of CO2 emissions in Indonesia and the number of foreign tourism (X2) has a positive and significant effect on the level of CO2 emissions in Indonesia.